Catalan sociolinguistics : state of the art and future challenges - Pradilla, Miquel Angel, 1961- (Amsterdam ; Philadelphia : John Benjamins Publishing Company, 2022)
"The aim of the work Catalan Sociolinguistics. State of the Art and Future Challenges is to give an account, in a summary way, of the major topics dealt with by the study of the relation between language and society in the Catalan language community, and the extent to which international approaches have been received and how they have been adapted to the Catalan domain. Every tradition has interpreted this interaction with specific approaches. The Catalan tradition, for example, has opted for a vision that integrates a wide range of studies on different themes (economy, law, political science, communication, ecology, linguistic variation, anthropology, and so on). So, in the book you are holding, the authors of the various chapters, recognised specialists in their fields, have provided complementary views that will enable us to make an overall analysis, something that was urgently needed in the context of the ultimate aim of bringing internal consistency to the discipline"--
Preface / Miquel Àngel Pradilla Cardona -- Catalan sociolinguistics: a multifaceted discipline / Miquel Àngel Pradilla Cardona -- History of the group GCS/ASOLC/SOCS / Francesc Vallverdú -- Linguistic ecology / Pere Comellas Casanova -- For a prospective sociology of language: from prophecy to foresight / Ernest Querol Puig -- Is there a social history of the Catalan language? / Miquel Nicolás -- Research on language codification: a general proposal / Joan Costa-Carreras -- The process of normalising Catalan in the media: notes on the evolution of research (1980-2020) / Josep Gifreu and Maria Corominas -- The (scant and scarcely recognised) contribution of political science to the study of the relationship between language and society in the Catalan-speaking area / Albert Branchadell -- Forty years of language policy in Catalonia (1980-2020): intervention in linguistic skills, practices and ideologies / Elvira Riera-Gil -- From normalisation to sustainability: the limits of status planning / Isidor Marí -- Language law in the Catalan domain / Eva Pons Parera -- The economics of language / Amado Alarcón Alarcón -- Demolinguistics in Catalan-speaking territories / Joaquim Torres i Pla -- The linguistic transmission of Catalan: current state of affairs and analysis / Antoni Mas i Miralles and Brauli Montoya Abat -- Research on educational sociolinguistics in the Catalan-speaking area / F. Xavier Vila -- Language and social psychology research in Catalan sociolinguistics / Llorenç Comajoan-Colomé and Miquel Strubell i Trueta -- Linguistic anthropology: concepts and field sites / Joan A. Argenter -- New speakers: language and subjectivity / Joan Pujolar -- Pragmatics and discourse analysis / Núria Alturo -- The kaleidoscopic universe of the sociolinguistics of variation in the Catalan language / Miquel Àngel Pradilla Cardona.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 29, 2022).
eBooks on EBSCOhost
Keywords: Catalan language -- Social aspects; Sociolinguistics -- Spain -- Catalonia; Catalan (Langue) -- Aspect social; Sociolinguistique -- Espagne -- Catalogne; Catalan language -- Social aspects; Sociolinguistics; Spain -- Catalonia; Essays; Essays